Model Pembelajaran Talking Stick untuk Meningkatkan Aktivitas dan Pemahaman Tentang Masa Penjajahan Belanda di Indonesia - Bijanti Bijanti (Jurnal Didaktika Pendidikan Dasar, 2023)
This study aims to improve student learning outcomes and activities in Social Sciences (IPS) subjects through the Talking Stick type cooperative learning model for fifth graders at SD Negeri Logandeng Karangdadap Pekalongan in 2019/2020. This research is a Classroom Action Research (CAR) with a cycle model that is carried out repeatedly and continuously. The subjects of this study were students of class V, totaling 29 students and the object was the student’s social studies learning outcomes. Methods of data collection is done through observation, tests, and documentation. The data analysis technique was carried out in quantitative descriptive and qualitative descriptive. The results showed an increase in social studies learning outcomes. The increase in learning outcomes can be seen from the students' learning mastery from the average score in the student's initial data, which is 47.24 and has learning mastery of 14% and at the end of the first cycle the average value of students becomes 64.13 with learning mastery to 24% and at the end of the second cycle the average value of students rose to 76.89 with student learning completeness reached 59%. The learning process in the classroom has also increased.